2014
DOI: 10.1038/ncomms6698
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and dynamic remodelling of the septin cytoskeleton during the cell cycle

Abstract: Septins perform diverse functions through the formation of filaments and higher-order structures. However, the exact architecture of septin structures remains unclear. In the budding yeast Saccharomyces cerevisiae, septins form an “hourglass” at the mother-bud neck before cytokinesis, which is converted into a “double ring” during cytokinesis. Here, using platinum-replica electron microscopy, we find that the early hourglass consists of septin double filaments oriented along the mother-bud axis. In the late ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
210
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(233 citation statements)
references
References 39 publications
18
210
0
5
Order By: Relevance
“…For example, purified Shs1-capped hetero-octamers form elaborate spirals, rings, and "bird nest" structures in vitro, whereas hetero-octamers capped with Shs1(S259D) form instead a meshwork-like structure with a regularly repeating pattern . Such a gauze-like arrangement of filaments (attributed to septins by antibody decoration) was observed at the bud neck when replicas of fixed yeast spheroplasts were examined after "unroofing" by freeze fraction and deep etching (Rodal et al 2005) and lattices of crisscrossed filaments thought to be septins have been seen in more recent EM analysis of the structures assembled at the bud neck (Bertin et al 2012;Ong et al 2014). However, when present as the sole source of Shs1, neither Shs1(S259A) nor Shs1(S259D) had any effect on the ability of Shs1 to support growth in three different Shs1-dependent strain backgrounds (Figure 1, D-F), and otherwise wild-type cells expressing either Shs1(S259A) or Shs1(S259D) as the sole source of this subunit have a normal morphology (data not shown).…”
Section: Phosphorylation Of Shs1 Within Its Cte Is Not Required For Fmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, purified Shs1-capped hetero-octamers form elaborate spirals, rings, and "bird nest" structures in vitro, whereas hetero-octamers capped with Shs1(S259D) form instead a meshwork-like structure with a regularly repeating pattern . Such a gauze-like arrangement of filaments (attributed to septins by antibody decoration) was observed at the bud neck when replicas of fixed yeast spheroplasts were examined after "unroofing" by freeze fraction and deep etching (Rodal et al 2005) and lattices of crisscrossed filaments thought to be septins have been seen in more recent EM analysis of the structures assembled at the bud neck (Bertin et al 2012;Ong et al 2014). However, when present as the sole source of Shs1, neither Shs1(S259A) nor Shs1(S259D) had any effect on the ability of Shs1 to support growth in three different Shs1-dependent strain backgrounds (Figure 1, D-F), and otherwise wild-type cells expressing either Shs1(S259A) or Shs1(S259D) as the sole source of this subunit have a normal morphology (data not shown).…”
Section: Phosphorylation Of Shs1 Within Its Cte Is Not Required For Fmentioning
confidence: 99%
“…Because loss of the function of these proteins prevents cytokinesis and cell septation, and they seemed to be integral components of the filamentous structures erected at the bud neck, they were dubbed septins (Sanders and Field 1994;Pringle 2008). Indeed, subsequent purification of these proteins from yeast (Frazier et al 1998), and their production as recombinant proteins in bacteria Versele and Thorner 2004;Farkasovsky et al 2005), demonstrated that Cdc3, Cdc10, Cdc11, and Cdc12 were necessary and sufficient for the formation of long-paired filaments in vitro (Bertin et al 2008) the bud neck in vivo (Bertin et al 2012;Ong et al 2014). Detailed ultrastructural analysis led to the discovery that the septin complex that is the fundamental building block of the yeast filaments is a linear, hetero-octameric rod, with the order Cdc11-Cdc12-Cdc3-Cdc10-Cdc10-Cdc3-Cdc12-Cdc11 (Bertin et al 2008), which polymerizes end-on-end via Cdc11-Cdc11 interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Andrew Goryachev (University of Edinburgh, UK) presented new data showing that the septin collar is instrumental in maintaining the polarized segregation of Cdc42 activity not only in the bud, but also during bud growth in the S and G2 phases, thus extending the role that septins play during the cell cycle. Septins then assemble a highly ordered hourglass at the division site, which is remodelled into a double ring at the onset of cytokinesis (Ong et al, 2014).…”
Section: How Yeast Cells Sculpt and Use Septin Ringsmentioning
confidence: 99%
“…Septins are GTP-binding proteins involved in cytokinesis (1), membrane remodeling (2), and many other cellular events related to the cytoskeleton (3,4). They were first described in yeast (1), but subsequent studies with other eukaryotic organisms have revealed that septin genes are also ubiquitous in animals (5).…”
mentioning
confidence: 99%